2010
DOI: 10.1016/j.pain.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

N -Methyl-d-aspartate receptor (NMDAR) independent maintenance of inflammatory pain

Abstract: Following peripheral inflammation, NMDA receptor (NMDAR) activation in spinal cord dorsal horn neurons facilitates the generation of pain in response to low threshold inputs (allodynia) and signals the phosphorylation of protein kinase C (pPKC) and extracellular signal-regulated kinase 2 (pERK2). Intraplantar complete Freund's adjuvant (CFA) induces inflammatory nociception (allodynic pain) at 24 hours (h) with a concurrent increase in neuronal pPKCgamma and pERK2 but not glial pERK2. These effects are attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 36 publications
3
42
0
Order By: Relevance
“…p-ERK is sequentially activated in neurons, microglia, and astrocytes after spinal nerve ligation (Zhuang et al, 2005) and is also induced in spinal astrocytes in the late phase after CFA injection (Weyerbacher et al, 2010). P-p38 is expressed in spinal microglia after nerve injury (Clark et al, 2007;Jin et al, 2003) and acute inflammation (Svensson et al, 2003).…”
Section: Ho-1 Induction Reduces Activation Of Mapks and Production Ofmentioning
confidence: 99%
“…p-ERK is sequentially activated in neurons, microglia, and astrocytes after spinal nerve ligation (Zhuang et al, 2005) and is also induced in spinal astrocytes in the late phase after CFA injection (Weyerbacher et al, 2010). P-p38 is expressed in spinal microglia after nerve injury (Clark et al, 2007;Jin et al, 2003) and acute inflammation (Svensson et al, 2003).…”
Section: Ho-1 Induction Reduces Activation Of Mapks and Production Ofmentioning
confidence: 99%
“…Proinflammatory cytokines are associated with spinal NMDARcontaining nociceptive neurons activation and the maintenance of inflammatory pain (Weyerbacher et al, 2010;Ian et al, 2004;Zhang et al, 2008). It is convinced that inhalation of H 2 efficiently suppresses proinflammatory cytokines release (Huang et al, 2011;Ji et al, 2010), however, in clinical application, inhalation of H 2 gas is not convenient and is dangerous because of its flammable and explosive nature even at a concentration of 4.7% in air (Ohsawa et al, 2007).…”
mentioning
confidence: 99%
“…IL-6 was shown to be implicated in the initiation of inflammatory and neuropathic pain (Cui et al, 2000). It is demonstrated that proinflammatory cytokines have an excitatory action on the glutamatergic synaptic transmission and activation of NMDAR NR1 and NR2B subunits in the dorsal horn (Weyerbacher et al, 2010;Ian et al, 2004). IL-1␤ was indicated to be one of the crucial mediators of neuropathic pain acting through an acute modulation of NR1 activity (Zhang et al, 2008;Fukuoka et al, 1994).…”
mentioning
confidence: 99%
“…These increases were inhibited by intrathecal BAM8-22. Given that ERK (Wei et al, 2006;Weyerbacher et al, 2010) and PKC (Malmberg et al, 1997;Polgar et al, 1999) transduction pathways play a critical role in the hypersensitivity of spinal dorsal horn and/ or DRG neurons in peripheral inflammation, the above results may suggest that the activation of MrgC receptors inhibited central and peripheral sensitization.…”
Section: Inhibition Of Inflammatory Pain By Mrgc Receptorsmentioning
confidence: 91%
“…PKCg is the major isoform of PKC in the spinal dorsal horn and is expressed in nociceptive neurons in lamina II (Malmberg et al, 1997;Polgar et al, 1999). The injection of CFA in the periphery increases the expression of PKC in the spinal dorsal horn (Martin et al, 1999;Honore et al, 2000;Weyerbacher et al, 2010), whereas the inhibition of PKC reduces CFA-induced miniature excitatory postsynaptic currents and c-Fos expression in dorsal horn neurons (Giles et al, 2007). PKCg knockout mice display a reduced pain behavior and c-Fos expression in the spinal dorsal horn following formalin injection (Malmberg et al, 1997).…”
Section: Inhibition Of Inflammatory Pain By Mrgc Receptorsmentioning
confidence: 99%